Iron and nitrate-driven anaerobic methane oxidation in methane seep sediments of the Laptev Sea; Chemical Geology; Vol. 699 - Purgina D. V. Dariya Valerievna; Moiseeva Yu. A. Yuliya Aleksandrovna; Wild Birgit; Guseva N. V. Natalia Vladimirovna; Gershelis E. V. Elena Vladimirovna; Gustafsson O. Orjan; Khvaschevskaya A. A. Albina Anatolievna; Pakhomova S. V. Svetlana Vladimirovna; Kholodov V. A. Vladimir Alekseevich; Dudarev O. V. Oleg Viktorovich; Kosmach D. A. Denis Alekseevich; Chernykh D. S.; et al. (2026, 2026)
Title screen